2021
DOI: 10.3390/biology11010016
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Retinal Tissue in an S100B Autoimmune Glaucoma Model

Abstract: Glaucoma is a neurodegenerative disease that leads to damage of retinal ganglion cells and the optic nerve. Patients display altered antibody profiles and increased antibody titer, e.g., against S100B. To identify the meaning of these antibodies, animals were immunized with S100B. Retinal ganglion cell loss, optic nerve degeneration, and increased glial cell activity were noted. Here, we aimed to gain more insights into the pathophysiology from a proteomic point of view. Hence, rats were immunized with S100B, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Microglia are the macrophages of the CNS, yet it is known that microglia also have the ability of cellular cytotoxicity [122]. Recent proteomic data further confirmed that the immune system plays an important role in the pathology of glaucoma since a shift in the regulation was observed in several immune system-associated proteins after immunization with S100 calcium-binding protein B (S100B), including HSP60 [123]. Altogether, the immune system seems to be a promising target for new therapeutic approaches.…”
Section: The Experimental Autoimmune Glaucoma Modelmentioning
confidence: 99%
“…Microglia are the macrophages of the CNS, yet it is known that microglia also have the ability of cellular cytotoxicity [122]. Recent proteomic data further confirmed that the immune system plays an important role in the pathology of glaucoma since a shift in the regulation was observed in several immune system-associated proteins after immunization with S100 calcium-binding protein B (S100B), including HSP60 [123]. Altogether, the immune system seems to be a promising target for new therapeutic approaches.…”
Section: The Experimental Autoimmune Glaucoma Modelmentioning
confidence: 99%
“…Axon regeneration is inhibited by the suppressor of cytokine signalling (SOCS) suppressing the Jak/STAT signalling [101]. Interestingly, in an immunoreactive male Lewis rats for S100B protein (the antibody which is found in high titre in glaucoma patients) showed 43 proteins were dysregulated in the retina, out of which alpha-2 macroglobulin increase was significantly associated with heat shock protein 60, showcasing the role of immunological factors in glaucoma [102].…”
Section: Neuroprotection and Neurodegeneration Genomics In Glaucomamentioning
confidence: 99%
“…In addition, peptides can be quantified through automated data analyses with consistency and accuracy comparable with that of SRM (Gillette & Carr, 2013; Röst et al, 2017). Therefore, SWATH‐MS has become an emerging methodology introduced into several recent retina proteomics studies focused on oxygen‐induced retinopathy in mouse (Vähätupa et al, 2018; Xu et al, 2022), identification of differentially expressed proteins in the retinal emmetropization process in guinea pig (Shan et al, 2018), creation of spectral library of proteins for the normal C57BL/6 mouse retina (Sze et al, 2021), revealing the significance of lipid metabolism in myopic guinea pig retina (Bian et al, 2021), detecting and quantifying regional changes of retinal protein expressions after optic nerve injury in rats (Kwong et al, 2021), as well as proteomic analysis of retinal tissue in an S100B autoimmune glaucoma model (Reinehr et al, 2021).…”
Section: Ms‐based Proteomics To Catalog and Measure Protein Expressio...mentioning
confidence: 99%
“…However, the activation of the classical complement pathway and upregulation of cholesterol transport proteins were exclusive for the glaucomatous human retinae. In the most recent proteomics study focused on glaucoma using retinal tissue (Reinehr et al, 2021), DIA‐based LC‐MS/MS measurements showed a complex, time‐dependent regulations of protein expression in an S100B autoimmune model in rats with the TCA cycle and glutamate processing representing the main functional interactions related to the disease one and two weeks after immunization, respectively. The role of microglia in this model of glaucoma‐like degeneration of the retina also was addressed earlier through a label‐free shotgun proteomics study and using minocycline to inhibit inflammatory response (Grotegut et al, 2020).…”
Section: Proteomics Studies Focused On Biology Pathology and Therapy ...mentioning
confidence: 99%